Postural control during one-leg stance in active and sedentary older people - Leonardo George Victorio Victor; Márcio Rogério de Oliveira; Denilson de Castro Teixeira; Maria Amélia Paes; Dirce Shizuko Fujisawa; Nuno de Noronha da Costa Bispo; Rubens Alexandre da Silva Junior (Universidade Estadual Paulista (UNESP), 2014)
Physical inactivity and aging are functional disability factors for older individuals, causing loss of balance and increasing the risk of falls. The purpose of this study was to compare the balance of physically independent older individuals, both participants and non-participants in a regular exercise program. Fifty six physically independent older participants were divided into G1ACTIVE = 28 individuals who participate in a regular exercise program and G2SEDENTARY = 28 individuals who did not participate in any physical exercise program. All participants underwent an eyes-open during one-leg balance test on a force platform. The postural oscillation parameters included center of pressure (COP); sway mean velocity and frequency of COP oscillations. G2 SEDENTARY showed higher postural instability than G1ACTIVE. Significant differences were observed for the main balance parameters. The results of this study support the concept that participation in regular physical activity is beneficial for postural balance of older individuals.